Application of the Combined Learning Model of JIGSAW and AIR (Auditory, Intellectually, Repetition) Learning Methods in Social Sciences Subjects - Dinda Dwi Utami; Nur Alfiyani; Metro Lingga; Sudrajat, Sudrajat (JURNAL PENDIDIKAN IPS, 2023)
Research is an effort made by teachers to increase the effectiveness of learning carried out at SMPN 6 Pontianak. This research aims to test the effectiveness of learning by combining two methods, namely Jigsaw and Auditory, Intellectual, and Repetition (AIR). This research is classroom action research (PTK) with the objective being 27 students in class IX of SMPN 6 Pontianak, consisting of 15 male students and 12 female students. Meanwhile, the subject of this research is a class IX social studies teacher who acts as a researcher and observer in the learning process. The data collection method used is in the form of test techniques, observation, interviews, and documentation. This classroom action research was carried out in two cycles. The average class result in cycle I was 24.8 with a completion percentage of 3.7%, while the results in cycle II showed an average class score of 94.8 with a completion percentage of 88%. This means that the average class score has increased from 24.8 to 94.8 and the percentage of classical learning completion has increased from 3.7% to 88%. This shows that the combination of the two Jigsaw and Auditory, Intellectual, Repetition (AIR) methods is effectively used in the learning process and can even improve student learning outcomes.